Politics of Environmental Permit Law in Sustainable Development Perspective - Mulyani, Tri -; Muryati, Dewi Tuti; Triasih, Dharu - (Faculty of Law, Universitas Pekalongan, 2024)
In light of UUPPLH Articles 38 and 39, which provide that environmental permits may be withdrawn by the TUN court, the unclear paradigm raises severe concerns about the validity of environmental permission as the subject of a dispute amongst state officials. The Job Creation Law really refers to an Environmental Feasibility Decree (SKKL) or a Statement of Environmental Management Commitment (PKPLH) that has been approved by the federal and local governments, depending on the kind of environmental approval. Buildings that comply with the Job Creation Law and have received environmental approval in the form of a product meet the conditions to be considered for consideration as permits, as stated in Article 39, paragraph (2). The vague paradigm substantially calls into doubt the validity of environmental permission as the topic of a State Administrative dispute, given Articles 38 and 39 of the UUPPLH, which stipulate that environmental permits may be canceled through the TUN court. Depending on the kind of environmental approval, the Job Creation Law really refers to an Environmental Feasibility Decree (SKKL) or a Statement of Environmental Management Commitment (PKPLH) that has been accepted by the federal and municipal governments. Construction that conforms with the Job Creation Law and that obtains environmental approval in the form of a product meets the conditions to be declared suitable for consideration as a permit, as stated in paragraph (2) of Article 39.